A Bioinformatic Investigation of the Mechanism Underlying Migraine-Induced Erectile Dysfunction. (4th May 2021) - Wang, Ji-sheng; Deng, Sheng; Zhao, Qi; Zhang, Kai-ge; Bao, Bing-hao; Feng, Jun-long; Meng, Fan-chao; Dai, Heng-heng; Li, Xiao; Li, Hai-song; Wang, Bin
Abstract : Background . Over recent years, an increasing body of literature has focused on the relationship between erectile dysfunction (ED) and migraine. However, the specific mechanism is unclear. Materials and Methods . We used a bioinformatic database to predict the targets and pathways associated with migraine and ED. Twenty male SD rats were randomly divided into a blank group (Group A, n = 10 ) and a migraine model group (Group B, n = 10 ). The rats in Group A were subcutaneously injected with normal saline (2 ml/kg) into the back of the neck. Rats in Group B were subcutaneously injected with nitroglycerin 10 mg/kg (5 mg/ml) into the back of the neck in order to create an animal model of migraine. Next, we carried out the measurement of erectile function. We used hematoxylin and eosin (HE) to compare the tissue structure of the cavernous body of the penis. Western blotting was used to determine the expression levels of PI3K, p-AKT, and p-mTOR in the protein; Reverse Transcription-Polymerase Chain Reaction (RT-qPCR) was used to determine the expression levels of PI3K, AKT, and mTOR in the messenger ribonucleic acid (mRNA). Results . There are 117 intersection targets of migraine and ED, involving 188 cell biological processes (BP), 21 cellular components (CC), 31 molecular functions (MF), and 65 signaling pathways. HE staining results show that there were no significant differences between Group A and Group B with regard to any of the parameters. Compared with Group A, the levels of the PI3K, p-AKT, and p-mTOR proteins and PI3K, AKT, and mTOR mRNAs in Group B decreased (P < 0.01 ). Conclusions . The decline of erectile function in a rat model of migraine was associated with the PI3K/Akt/mTOR signaling pathway.